Comparative Study of Powder Carriers Physical and Structural Properties - Klára Kostelanská (Pharmaceutics, 2022)
High specific surface area (SSA), porous structure, and suitable technological characteristics (flow, compressibility) predetermine powder carriers to be used in pharmaceutical technology, especially in the formulation of liquisolid systems (LSS) and solid self-emulsifying delivery systems (s-SEDDS). Besides widely used microcrystalline cellulose, other promising materials include magnesium aluminometasilicates, mesoporous silicates, and silica aerogels. Clay minerals with laminar or fibrous internal structures also provide suitable properties for liquid drug incorporation. This work aimed at a comparison of 14 carriers’ main properties. Cellulose derivatives, silica, silicates, and clay minerals were evaluated for flow properties, shear cell experiments, SSA, hygroscopicity, pH, particle size, and SEM. The most promising materials were magnesium aluminometasilicates, specifically Neusilin® US2, due to its proper flow, large SSA, etc. Innovative materials such as FujiSil® or Syloid® XDP 3050 were for their properties evaluated as suitable. The obtained data can help choose a suitable carrier for formulations where the liquid phase is incorporated into the solid dosage form. All measurements were conducted by the same methodology and under the same conditions, allowing a seamless comparison of property evaluation between carriers, for which available company or scientific sources do not qualify due to different measurements, conditions, instrumentation, etc.